Pelaksanaan Supervisi Akademik Berbasis Digital Di SMPN 7 Sijunjung - Refnawati Refnawati; Sirajul Munir; Jamilus Jamilus; Adripen Adripen; Nina Suzanne (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to describe the implementation of digital-based academic supervision at SMPN 7 Sijunjung in improving teacher professionalism and learning quality. The study used a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation involving the principal, vice principal, teachers, and school staff. Data analysis used the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that digital-based academic supervision was implemented systematically through the use of Microsoft Excel, Google Form, Google Drive, Google Meet, and Google Classroom. The implementation stages included pre-observation, classroom observation, and post-observation integrated with digital documentation. Supervision evaluation was conducted based on digital data to objectively identify teacher strengths and weaknesses. Obstacles faced included limited internet connection and variations in teachers' digital literacy. However, the school overcame these through training and mentoring in the use of digital technology. The research findings indicate that digital-based academic supervision can improve the effectiveness of supervision implementation, learning documentation, and teacher professional development on an ongoing basis.